Interdisciplinary Outreach of Library and Information Science Research as Reflected in “Essential Science Indicators” - Tabatabaei, Nahid; Beheshti, Jamshid (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper investigates the contribution of LIS research to intellectual growth of other disciplines. 209 highly cited papers has been analyzed to reveal the interdisciplinary patterns. Interdisciplinary journals seem more promising in producing highly cited papers. Cet article analyse la contribution de la recherche en BSI en ce qui concerne la croissance intellectuelle d’autres disciplines. 209 articles fréquemment cités ont été analysés afin de révéler les modèles interdisciplinaires. Les périodiques interdisciplinaires semblent plus prometteurs pour la production d’articles couramment cités.